Survey of isolation room equipment and resources in an academic hospital. Issue 6 (8th July 2019) - Telford, Brittany; Healy, Ray; Flynn, Ellen; Moore, Emma; Ravi, Akshaya; Geary, Una
Abstract : Purpose: The purpose of this paper, a point prevalence study, is to quantify the incidence of isolation and identify the type of communicable diseases in isolation. The paper evaluates isolation precaution communication, availability of personal protective equipment (PPE) as well as other equipment necessary for maintaining isolation precautions. Design/methodology/approach: A standardised audit tool was developed in accordance with the National Standards for the Prevention and Control of Healthcare Associated Infections (May 2009). Data were collected from 14 March 2017 to 16 March 2017, through observation of occupied isolation rooms in an academic hospital in Dublin, Ireland. The data were subsequently used for additional analysis and discussion. Findings: In total, 14 per cent (125/869) of the total inpatient population was isolated at the time of the study. The most common isolation precaution was contact precautions (96.0 per cent). In all, 88 per cent of known contact precautions were due to multi-drug resistant organisms. Furthermore, 96 per cent of patients requiring isolation were isolated, 92.0 per cent of rooms had signage, 90.8 per cent had appropriate signs and 93.0 per cent of rooms had PPE available. Finally, 31 per cent of rooms had patient-dedicated and single-use equipment and 2.4 per cent had alcohol wipes available. Practical implications: The audit tool can be used to identify key areas of noncompliance associated with isolation and inform continuous improvement and education. Originality/value: Currently, the rate of isolation is unknown in Ireland and standard guidelines are not established for the evaluation of isolation rooms. This audit tool can be used as an assessment for isolation room compliance.